Energy consumption, thermal utilization efficiency and hypericin content in drying leaves of St John’s Wort (Hypericum Perforatum) - Minaei, Saeid; Chenarbon, Hossein Ahmadi; Motevali, Ali; Hosseini, Akbar Arab (Journal of Energy in Southern Africa, 2014)
Massive consumption of energy in the drying industry has prompted extensive research regarding various aspects of drying energy and requirements. Thermal utilization efficiency, specific energy requirement, total energy consumption and hypericin content in drying of St John’s Wort were determined using a hot-air dryer. Experiments were conducted at four air temperature levels (40, 50, 60, and 70°C), three air velocities (0.3, 0.7, and 1 m/s) and three sample thicknesses (1, 2 and 3 cm). Based on the results of data analysis, minimum and maximum levels of energy consumption were 0.56 and 3.24 kWh, respectively. The required specific energy decreased with increasing sample thickness. The minimum and maximum required specific energies were 4.41 and 17.53 for 2 cm thick and 4.28 and 13.67 for 3 cm thick layers (kWh/kg), respectively. The maximum and minimum values of thermal utilization efficiency in different treatments were found to be 14% and 72%, respectively. Hypericin content decreased with increasing temperature and increased with air velocity and product sample thickness, so that the minimum and maximum hypericin amounts were 67 and 355 ppm, respectively.